2023
DOI: 10.1289/ehp11120
|View full text |Cite
|
Sign up to set email alerts
|

Association between First Trimester Exposure to Ambient PM2.5 and NO2 and Congenital Heart Defects: A Population-Based Cohort Study of 1,342,198 Live Births in Canada

Abstract: Background: The extent to which ambient air pollution contributes to the pathogenesis of congenital heart defects remains uncertain. Objective: We investigated whether first trimester exposure to ambient fine particulate matter ( ) and nitrogen dioxide ( ) was associated with the risk of critical and noncritical heart defects in a large population-based cohort of births. Methods: We carried out a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The first trimester of the pregnancy was identified as a critical period for fetal heart development. Case-control and time-series studies from China and a cohort study from America have observed a higher risk of CHDs in infants was associated with higher concentrations of PM 2.5 exposure during the first trimester. , However, time-series studies and case-control studies in China confirmed a correlation between increased morbidity of CHD and exposure to PM 2.5 during the second and third trimester. Another case-control study from China found a higher risk of CHD in offspring associated with higher concentrations of PM 2.5 exposure during preconception . On the contrary, case-control studies from America and China reported a reduced risk of ventricular septal defect (VSD) and atrial septal defect (ASD) associated with PM 2.5 exposure during pregnancy. , A study conducted in Israel demonstrated that PM 2.5 exposure decreased the risk of patent ductus arteriosus (PDA) .…”
Section: The Aop On Pm25 Induced Cardiac Developmental Toxicitymentioning
confidence: 99%
“…The first trimester of the pregnancy was identified as a critical period for fetal heart development. Case-control and time-series studies from China and a cohort study from America have observed a higher risk of CHDs in infants was associated with higher concentrations of PM 2.5 exposure during the first trimester. , However, time-series studies and case-control studies in China confirmed a correlation between increased morbidity of CHD and exposure to PM 2.5 during the second and third trimester. Another case-control study from China found a higher risk of CHD in offspring associated with higher concentrations of PM 2.5 exposure during preconception . On the contrary, case-control studies from America and China reported a reduced risk of ventricular septal defect (VSD) and atrial septal defect (ASD) associated with PM 2.5 exposure during pregnancy. , A study conducted in Israel demonstrated that PM 2.5 exposure decreased the risk of patent ductus arteriosus (PDA) .…”
Section: The Aop On Pm25 Induced Cardiac Developmental Toxicitymentioning
confidence: 99%
“…In their study published in this issue, Buteau et al. 8 used a retrospective registry-based cohort to analyze data for 1,342,198 live births, including 12,715 with CHDs, from Quebec, Canada. They found that maternal exposure to fine particulate matter and nitrogen dioxide in the first trimester was associated with an increased risk of noncritical CHDs (particularly atrial septal defects) in mothers with comorbidities (particularly anemia, preeclampsia, and preexisting hypertension).…”
mentioning
confidence: 99%